Risks of enteral nutritional therapy: a clinical simulation - Ana Paula Almeida Corrêa; Carlise Rigon Dalla Nora; Gabriele Peres de Sousa; Valessa Jamile dos Santos; Graziela Lenz Viegas; José Luís Díaz Agea; Adriana Catarina de Souza Oliveira; Mariur Gomes Beghetto
Abstract Objective: Knowing the perceptions of nursing technicians about the risks to the patient in the use of enteral nutritional therapy, in a scenario of clinical simulation. Method: A qualitative study, performed through a clinical simulation with nursing technicians from a university hospital in the South of Brazil, in August 2017. The simulation sessions were recorded in audio and later transcribed. Content analysis was used for data analysis. Results: Four thematic categories resulted from the analysis: Risks related to the tube; Risks related to diet; Risks related to contamination and Risks related to routine. Conclusion: The clinical simulation allowed nursing technicians to identify risks in the practice of enteral nutritional therapy and ways to minimize them. Promoting spaces for continuing education in the service, using clinical simulation methodology, gives an opportunity for critical reflection, which can contribute to safer, effective and quality nursing care.